Doing Casual Sex: A Sexual Fields Approach to the Emotional Force of Hookup Culture. (16th December 2019) - Wade, Lisa
Abstract: Sex on college campuses has emerged as a source of emotional distress for students. This paper adopts a sexual fields approach to offer a gendered analysis of hookup culture's central emotional imperative: to be casual about sex. Based on 101 first-person accounts of sex and relationships in college, the findings reveal how students enact sexual casualness by hooking up only when drunk, refraining from tenderness, being unfriendly afterward, and avoiding "repeat" hookups. Students both break and follow these rules. Breaking them is a primary way they form romantic relationships, but also a source of stigma, especially for women. This process helps explain some of the negative emotional consequences of hookup culture, as well as how hookup culture suppresses relationship formation and friends-with-benefits arrangements. The descriptive account of how students "do" casual sex adds much needed interactive detail to the literature on hooking up, while also contributing to sexual field theory. The findings add an emotional dimension to literature on the structure of desire, document a sexual field that fails to reflect the majority of its participants' desires, and reveal that a sexual field can be resilient, and possibly even strengthen, even in the face of widespread dissatisfaction.